Cigarette Smoking and Mortality in Patients With Pancreatic Cancer: A Systematic Review and Meta-analysis. Issue 8 (September 2019) - Ben, Qi-Wen; Liu, Jun; Sun, Yun-Wei; Wang, Li-Fu; Zou, Duo-Wu; Yuan, Yao-Zong
Abstract : Abstract: Current evidence on cigarette smoking associated with pancreatic cancer mortality is limited. We searched MEDLINE, Web of Science, and Embase databases to identify relevant studies published through January 31, 2018. A random-effects model was used to estimate summary hazard ratios (HRs) and 95% confidence intervals (CIs). A total of 20 studies were retrieved, involving 2, 517, 623 participants. Of these, more than 15, 341 patients with pancreatic cancer died. Compared with never smokers, current (summary HR, 1.56; 95% CI, 1.34–1.83) and former (summary HR, 1.15; 95% CI, 1.06–1.26) smokers had elevated risk of total mortality in patients diagnosed with pancreatic cancer. This effect of cigarette smoking is observed both in the Western regions and the Asia-Pacific regions. This effect of smoking is independent of alcohol use, body mass index, and history of diabetes but is modified by tumor stage and study settings. Dose-response associations between smoking and pancreatic cancer mortality were revealed for smoking intensity, cumulative amount of cigarettes smoked, and duration of smoking. Cigarette smoking was associated with an increase in total mortality for patients with pancreatic cancer. Future studies should further clarify the role of smoking as an effect modifier in treatment trials of pancreatic cancer. Abstract : Supplemental digital content is available in the text.